2022
DOI: 10.1186/s12936-022-04144-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the safety, impact and effectiveness of RTS,S/AS01E malaria vaccine following its introduction in three sub-Saharan African countries: methodological approaches and study set-up

Abstract: Background Following a 30-year development process, RTS,S/AS01E (GSK, Belgium) is the first malaria vaccine to reach Phase IV assessments. The World Health Organization-commissioned Malaria Vaccine Implementation Programme (MVIP) is coordinating the delivery of RTS,S/AS01E through routine national immunization programmes in areas of 3 countries in sub-Saharan Africa. The first doses were given in the participating MVIP areas in Malawi on 23 April, Ghana on 30 April, and Kenya on 13 September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…This new strategy is leading to reduced new malaria cases worldwide [ 9 ]. Recent study on the vaccination campaign impact reports that in a population of children from 5 months age, who received all four doses of malaria vaccine, in a follow-up time of 4 years, they observed a reduction in both clinical and severe malaria cases of 39% and 29%, respectively [ 10 ].…”
Section: Malaria Diagnosismentioning
confidence: 99%
“…This new strategy is leading to reduced new malaria cases worldwide [ 9 ]. Recent study on the vaccination campaign impact reports that in a population of children from 5 months age, who received all four doses of malaria vaccine, in a follow-up time of 4 years, they observed a reduction in both clinical and severe malaria cases of 39% and 29%, respectively [ 10 ].…”
Section: Malaria Diagnosismentioning
confidence: 99%
“…The development of an anti-malarial vaccine is important for regional malaria elimination and future eradication efforts. Malaria vaccine policy is a global effort, and the vaccine has already been applied to a large number of children in Ghana, Kenya, and Malawi [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts to evaluate the effectiveness, cost-effectiveness, efficacy and safety impact of malaria vaccines implemented in the three regions of Ghana, Kenya, and Malawi [ 15 , 16 ]. The pilot programme coordinated by the WHO indicates that the vaccine is successful in terms of safety and feasibility [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results from a large Phase III clinical study have shown that 4 doses of the vaccine present relatively modest and rapidly waning 25.9% and 17.3% effectiveness against clinical and severe malaria, respectively, in newborns aged 6–12 weeks, and 36.3% and 32.2% efficiency against clinical and severe malaria, respectively, in children aged 5–17 months [( 3 ) and reviewed in ( 4 )]. A post-approval plan comprising 4 complementary Phase IV studies that will evaluate safety, effectiveness and impact of RTS,S in the context of its real-life implementation will support the ongoing evaluation of the vaccine’s benefit-risk and inform decision-making for its potential wider implementation across sub-Saharan Africa ( 5 ). Moreover, RTS,S is not expected to protect against the other human malaria parasites, namely P. vivax (Pv), P. ovale , P. malariae , and the zoonotic P. knowlesi ( 6 ).…”
Section: Introductionmentioning
confidence: 99%